Arpenter et sillonner les archives du Web - Valérie Schafer (Les Cahiers de Framespa)
This article analyzes in three steps, each one corresponding to a specific methodological approach to Web archives, the way research on this born digital heritage has evolved under the double influence of new modes of archiving and access, developed by institutions, and of research questions. It looks back at research projects, from the Web90 project running between 2014 and 2018, dedicated to the digital cultures of the 1990s, to the current Hivi project (A History of Online Virality), through research about events (terrorist attacks of 2015-2016; COVID-19 crisis). This path is related to the evolution of the state of the art and of archival and academic practices, in the face of the large amounts of data generated, particularly those of the social networks, and of transnational or transversal research in progress.